Oral Mycosis Fungoides: Report of 2 Cases and Review of the Literature - Carolina Alexander-Savino; Alexandra Boye-Doe; Edith Bowers; Anne Beaven (Karger Publishers, 2023)
Oral and laryngeal cutaneous T-cell lymphoma (CTCL) is rare and usually associated with poor prognosis. Here, we discuss 2 cases of oral CTCL that developed in heavily pretreated patients and provide a review of the literature. The first case is of a 46-year-old African American male with rapidly progressive disease, presenting with a lesion on his hard palate 6 months after being diagnosed with a CD4+CD8+ CTCL. His cutaneous disease was widespread with tumors on >80% of his body surface area. Unfortunately, the patient died 2 ½ years after his CTCL diagnosis and 7 months after developing the oral CTCL lesion. The second case is of a 38-year-old African American male with stage IIb CD3+CD4+CD30+ mycosis fungoides (MF), who developed a tumor on the hard palate 6 months after diagnosis. He received palliative radiation to the oral lesion and multiple lines of systemic therapy for pulmonary, laryngeal, esophageal, and gastric involvement. Biopsy of the gastric lesions showed a CD30+ T-cell lymphoma with the same clonal peak as in his skin but with large cell transformation. Brentuximab vendoin was started, and the patient is now in complete remission, 30 months later. From the 76 cases of oral CTCL that have been reported in the English language, six were of transformed MF. The most common sites affected were the tongue and palate, and the most common presentation were erythematous or ulcerated tumors, plaques, or nodules associated with dysphagia and pain. Oral CTCL typically occurs years after the initial diagnosis of CTCL and portend a poor prognosis with an average survival of just over 1 year after development of oral lesions.